Highly selective water channel activity measured by voltage clamp: Analysis of planar lipid bilayers reconstituted with purified AqpZ - Pohl, Peter (National Academy of Sciences, 2001)
Aquaporins are membrane channels selectively permeated by water or water plus glycerol. Conflicting reports have described ion conductance associated with some water channels, raising the question of whether ion conductance is a general property of the aquaporin family. To clarify this question, a defined system was developed to simultaneously measure water permeability and ion conductance. The Escherichia coli water channel aquaporin-Z (AqpZ) was studied, because it is a highly stable tetramer. Planar lipid bilayers were formed from unilamellar vesicles containing purified AqpZ. The hydraulic conductivity of bilayers made from the total extract of E. coli lipids increased 3-fold if reconstituted with AqpZ, but electric conductance was unchanged. No channel activity was detected under voltage-clamp conditions, indicating that less than one in 10(9) transport events is electrogenic. Microelectrode measurements were simultaneously undertaken adjacent to the membrane. Changes in sodium concentration profiles accompanying transmembrane water flow permitted calculation of the activation energies: 14 kcal/mol for protein-free lipid bilayers and 4 kcal/mol for lipid bilayers containing AqpZ. Neither the water permeability nor the electric conductivity exhibited voltage dependence. This sensitive system demonstrated that AqpZ is permeated by water but not charged ions and should permit direct analyses of putative electrogenic properties of other aquaporins.